Analisis Faktor yang Berhubungan dengan Pemanfaatan Pelayanan Kesehatan di Wilayah Kerja Puskesmas Silalahi - Nasution, Dian Permata; Napitu, Marolop Parlindungan; Purba, Yeni Trisna; Ginting, Isaharpika Br; Gultom, Calvin (Jurnal Riset Hesti Medan, 2024)
One indicator for assessing how community health centers are utilized as healthcare facilities is the number of visits by the community to those centers. A low number of visits indicates that the community is underutilizing healthcare services. Over the past three years, from 2018 to 2020, the utilization of the Silalahi Community Health Center has seen a decline in the number of visits, from 45.8% in 2018, to 38.5% in 2019, and to 33.2% in 2020. This is attributed to the community’s misperception of illness. The objective of this study is to identify the factors associated with the utilization of health services at the Silalahi Community Health Center. This is a descriptive study using a cross-sectional design with a quantitative approach. The sample consisted of 95 respondents; cluster random sampling was used, and a questionnaire served as the data collection instrument. Data were analyzed using the Chi-Square test. The results indicate a significant association between Accessibility (p=0.001), Health Insurance Coverage (p=0.000), and Perception of Illness (p=0.000) with the utilization of health services. Age (p=0.083), Education (p=0.122), Occupation (p=0.093), and Availability of Health Personnel (p=0.368) showed no association with the utilization of health services. Recommendations are provided to the Health Office and Silalahi Community Health Center to further enhance health promotion efforts to improve public knowledge regarding the functions of the Community Health Center and perceptions of illness.